2008
DOI: 10.4049/jimmunol.180.1.559
|View full text |Cite
|
Sign up to set email alerts
|

Commensal Gut Flora Drives the Expansion of Proinflammatory CD4 T Cells in the Colonic Lamina Propria under Normal and Inflammatory Conditions

Abstract: We tested in B6 mice whether the local expansion of CD4 T cells producing proinflammatory cytokines including IL-17 (Th17 cells) in the colonic lamina propria (cLP) depends on the commensal microflora. High numbers of CD4 Th17 cells were found in the lamina propria of the ileum and colon but not the duodenum, jejunum, mesenteric lymph nodes, spleen, or liver of specific pathogen-free (SPF) mice. The microflora is required for the accumulation of cytokine (IL-17, IFN-␥, TNF-␣, IL-10)-producing CD4 T cells in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
128
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(138 citation statements)
references
References 59 publications
9
128
1
Order By: Relevance
“…In this regard, the numbers of IL-17A producing TH17 cells is reduced in the lamina propria of GF animals [70] . Because commensal flora is a major driving force of the homeostatic proliferation of naïve T cells in the periphery, the reduced cellularity in the immune system of GF mice may be the result of the deficient peripheral expansion of recent thymic T cell emigrants [71,72] .…”
Section: Immune Responses To the Commensal Floramentioning
confidence: 96%
See 1 more Smart Citation
“…In this regard, the numbers of IL-17A producing TH17 cells is reduced in the lamina propria of GF animals [70] . Because commensal flora is a major driving force of the homeostatic proliferation of naïve T cells in the periphery, the reduced cellularity in the immune system of GF mice may be the result of the deficient peripheral expansion of recent thymic T cell emigrants [71,72] .…”
Section: Immune Responses To the Commensal Floramentioning
confidence: 96%
“…Studies in which TH1 and TH17 cells were generated co-cultures, in which naïve T cells were cultured with fecal extracts pulsed DCs, and in the presence of TH1 or TH17 promoting cytokines indicated that TH17 cells are more pathogenic than TH1 cells [118] . Recent published observations report that colitis induced by transfer of IFNγ-deficient T cells in RAG -/-mice is associated with elevated numbers of TH17 cells in the lamina propria [70] . The adoptive transfer of IL-17F, but not IL-17A deficient CD4 T cells ameliorated the IBD in the transfer model [119,120] .…”
Section: Dcs In Ibdmentioning
confidence: 99%
“…Th17 cells may also contribute to the pathogenesis of enterocolitis in IL-10-deficient mice (56). IL-23 induces the differentiation of naive CD4 ϩ T cells into Th17 cells (57).…”
Section: Discussionmentioning
confidence: 99%
“…segmented filamentous bacteria, have been reported to induce this IL-17-secreting CD4 + T-cell subset. [28][29][30] Interleukin-23 has also been reported to inhibit the accumulation of intestinal Foxp3 + regulatory T (Treg) cells, a population of CD4 + T cells of importance for maintaining intestinal homeostasis. 31 Hence, using the Tcell transfer model of colitis, in which disease is induced in T-cell-deficient Rag (Fig.…”
Section: Interleukin-23 Has Broad Effects On Both T Cells and Non-t Cmentioning
confidence: 99%